Correlation Between Boron Contents of Soils and Wheat Plants (Triticum spp.) in The Cukurova Plain in Turkey - IRMAK, S.; VAPUR., H. (Asian Journal of Chemistry, 2010)
In this study, the correlation between boron contents of soil and boron contents of the wheat (Triticum spp.) in the Cukurova Region of Turkey has been reported. The soil samples were taken from the root area of the plants and collected leafs and grains samples of the same plants were analyzed for boron contents. The leaf samples taken during the stem elongation time and the grain samples taken at the maturation time were also analyzed. The boron contents of soil of samples were between 0.96 and 2.69 mg kg-1, but the boron contents of soil of some samples were measured under the critical level which is 1.00 mg kg-1. Whereas boron contents of leaves of wheat samples were obtained from 1.62 to 18.73 mg kg-1 and the boron contents of grain of wheat samples were obtained from 2.6 to 9.1 mg kg-1. There are an inverse relation between boron contents of soil, boron contents of leaves and boron contents of grain, respectively. Also, correlation between boron contents of soil and boron contents of leaves is significant at the 0.01 level according to statistical analysis. An addition, linear regression analysis was performed between dependent variable (boron contents of soil), independent variable (boron contents of leaves and boron contents of grain). F test and t- test using ANOVA was shown that significant values of each test are very practicable.